KELAS ASYIK DENGAN PERMAINAN KLASIK: METODE INOVATIF UNTUK PEMBELAJARAN BAHASA INGGRIS INTERAKTIF DI SDN 11 DAUH PURI - Ni Made Verayanti Utami; Ni Wayan Suastini; Ni Luh Vira Nitya Rini; Anak Agung Made Indrawati (Fakultas Bahasa Asing, 2024)
This community service aims to increase the effectiveness and engagement of students in learning English through the application of classic game methods. The scope of the service covers English teaching in grades 1 to 6 of SDN 11 Dauh Puri with a focus on the use of classic games, such as